A Study of the Content Appropriateness of the Textbooks of FLN Prepared by Maharashtra in Light of NEP 2020 Recommendations - Tripathi, Shruti (THE PRIMARY TEACHER, 2022)
The NEP 2020 has brought significant changes to the Indian education system, emphasising the importance of foundational skills development and the preparation of modern and quality textbooks to achieve the target of lifelong learning and holistic development. Foundational Literacy and Numeracy (FLN) are an integral part of the development of the abilities of children. They are like milestones in the learning curve of a child’s personality. Students who are well versed in both these aspects will essentially do well when they are required to connect new knowledge with already existing knowledge. The present study is based on the mandate of the NEP 2020 which suggests a primary focus on foundational literacy and numeracy. This research paper presents a comprehensive study examining the content appropriateness of the textbooks developed by the State Council of Educational Research and Training, Pune, Maharashtra in the context of the National Education Policy (NEP) 2020 recommendations. The emphasis of this research is on gaining insight into teachers’ experiences and perceptions of what a textbook should be like. To ascertain more about the range of perspectives, a questionnaire on a four-point scale was given out to teachers teaching at the Foundational Stage with different questions, covering content appropriateness of FLN. The research concludes with a set of actionable recommendations to enhance the content appropriateness of FLN textbooks in line with NEP 2020 guidelines. By addressing these suggestions, Maharashtra’s education system can take significant strides towards providing a more comprehensive and inclusive learning experience, empowering students with the essential foundational skills needed for lifelong learning and success